Observasi Sarana Prasarana Pjok di SMP N 1 Sedayu Tahun 2023 - Fajar Sodiq; Dody Tri Iwandana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
PJOK subjects are very important in learning, for achievement in learning requires sports facilities and infrastructure that are adequate and available. If there are no facilities and infrastructure, it will become a significant obstacle for teachers and students, because it hinders the learning process. The lack of facilities and infrastructure will hinder the movement of students, students will queue up to use the equipment. So that students will get bored participating in PJOK learning. Then the facilities and infrastructure must be adjusted to the number of students and condition them properly. The purpose of this study was to describe the availability of facilities and infrastructure at SMP N 1 Sedayu by using descriptive research methods and using observation and interview approach instruments. From the results of the research, the availability of PJOK facilities and infrastructure at SMP N 1 Sedayu is very complete and complete and meets the infrastructure standards for junior high schools of the same level as stated in the Regulation of the Minister of National Education number 24 of 2007. Keywords: Facilities and Infrastructure